Reinventing African Chieftaincy in the Age of AIDS, Governance, Gender, and Development - Quinlan, Tim; Ray, Donald I.; Sharma, Keshav; Clarke, Tacita (Africa: Missing Voices, 2011)
This collection of essays examines the relatively new, and frequently overlooked, political phenomenon in post-colonial Africa of chieftaincy "re-inventing" itself. The traditional authority of chiefs has been one of Africa's missing voices who are now bringing new resources to the challenges that AIDS, gender, governance, and development pose to the peoples of Africa. d This publication presents new research in Ghana, Botswana, and South Africa, providing the broadest geographic African coverage on the topic of African chieftaincy. The nineteen authors, many of them emerging scholars from Africa, are all members of the Traditional Authority Applied Research Network (TAARN). Their essays give critical insight into the transformation processes of chieftaincy from the end of the colonial/apartheid periods to the present. They also examine the realities of male and female traditional leaders in reinventing their legitimacy and their political offices in the age of great social and political unrest, health issues and governance and development challenges.